Cement composition and method for producing concrete products
A cement composition incorporating Awin, Beelite, and anhydrous gypsum in specific ratios addresses the challenge of achieving steam-cured concrete strength without steam curing, maintaining flowability, and reducing costs.
Patent Information
- Application Number
- JP2021027808
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-02-24
AI Technical Summary
Existing cement compositions struggle to achieve strength equal to or greater than the demolding strength of steam cured concrete products without the need for steam curing, while maintaining flowability and reducing manufacturing costs.
A cement composition containing a specific ratio of Awin, Beelite, and anhydrous gypsum, with a molar ratio of anhydrous gypsum to Awin ranging from 2.5 to 6.0, which enhances the initial strength of cement without the need for steam curing.
The cement composition achieves strength equal to or greater than the demolding strength of steam cured concrete products, with minimal reduction in flowability, and reduces manufacturing costs by eliminating the need for steam curing.
Smart Images

Figure 0007664709000001 
Figure 0007664709000002 
Figure 0007664709000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a strength-enhancing agent for cement containing Awin, a cement composition, a method for producing the cement composition, and a method for producing a concrete product containing the cement composition. [Background technology]
[0002] In order to speed up demolding and shipping of concrete products, concrete product manufacturing plants usually perform steam curing as the final stage of production. However, in order to reduce the cost of heavy oil consumed in steam curing and to improve the working environment by not using high-temperature steam, there is a demand for cement that has strength development equal to or greater than the strength of steam-cured concrete products when they are demolded (hereinafter referred to as "demolding strength"), even without steam curing.
[0003] Conventionally, one of the means for improving the early strength development of cement is to add an early strength admixture to the cement. For example, Non-Patent Document 1 discloses an early-strengthening admixture whose main component is CaO (CaO content is 89.7 parts by mass). When this early-strengthening admixture is added to ordinary Portland cement, the strength after 7 days is higher than that of ordinary Portland cement with steam curing even without steam curing, but the initial strength development at an age of about 6 hours cannot be said to be high. Furthermore, Patent Document 1 proposes a cement composition in which calcium sulfoaluminate such as 3CaO·3Al2O3·CaSO4 is added to Portland cement to increase early strength. However, this cement composition has the problem that fluidity decreases as the amount of calcium sulfoaluminate added increases, and that an organic acid or the like must be added to improve this fluidity, which increases production costs. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Sato, M. et al., "Strength Development Mechanism of Concrete Using High-Early-Strength Admixtures," Proceedings of the Japan Concrete Institute, Vol. 24, No. 1, 2002 [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 09-48649 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide a cement composition that exhibits strength development without steam curing that is equal to or greater than the form-removal strength of a steam-cured concrete product, and a strength-enhancing agent for cement for producing the cement composition. [Means for solving the problem]
[0007] The inventors of the present invention considered that in order to improve the early strength of cement more than that of existing cements, it would be necessary to change the mineral composition or add admixtures to a cement composition that has strength development equal to or greater than the form-stripping strength of steam-cured concrete products even without steam curing. Therefore, they focused on Awin (3CaO·3Al2O3·CaSO4, abbreviated as C4A3$) as a strength enhancer for cement that improves the very early strength development at about 6 hours of age, and examined its application to the cement. As a result, they found that concrete using a strength enhancer for cement and a cement composition containing Awin, belite (2CaO·SiO2, abbreviated as C2S), and anhydrous gypsum (CaSO4, abbreviated as C$) in a specific ratio has strength development equal to or greater than the form-stripping strength of steam-cured concrete even without steam curing, and thus completed the present invention. That is, the present invention is a strength enhancer for cement having the following configuration.
[0008] [1] The following cement strength enhancers: 20 to 45 parts by mass and cement 55 to 80 parts by mass A cement composition comprising: Awin 9.5 ~15 Mass % Alite 34 ~ 40 mass%, A total of 45-55 mass% of awin and alite, 4-8 mass% of aluminate phase, 5-15 mass% of ferrite phase, and anhydrous gypsum, and the molar ratio of the content of the anhydrous gypsum to the content of the awin is 2.5 to 6.0, and the Blaine specific surface area is 3200 to 3700 cm 2 / g of the cement composition. [Strength enhancer for cement] A strength enhancer for cement comprising at least awin, belite, and anhydrous gypsum, The composition contains 36 to 49 parts by mass of awin, 18 to 25 parts by mass of belite, and a molar ratio of the anhydrite content / the awin content is 2.5 to 6.0. [2] The above-mentioned [ 1 ] The cement composition described in the above. [3] The cement composition is for use in concrete products. 1] or [2 ] The cement composition described in the above. [4] The above [ 1 ]~[ 3 a mixing step of mixing the cement composition according to any one of the preceding items with at least fine aggregate, coarse aggregate, and water to obtain an unhardened concrete composition; A filling step of filling the unhardened concrete composition into a formwork; A curing step of curing the unhardened concrete composition at a temperature of 10 to 50°C to obtain a hardened concrete composition; and A demolding step of demolding the hardened body of the concrete composition; A method for producing a concrete product comprising at least the steps of: Effect of the Invention
[0009] Concrete containing a cement composition including the strength enhancer for cement of the present invention exhibits little decrease in fluidity, and even without steam curing, exhibits strength development equal to or greater than the form-removal strength of steam-cured concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] As described above, the present invention relates to a strength enhancer for cement containing at least specific amounts of awin, belite, and anhydrous gypsum, etc. Hereinafter, the strength enhancer for cement, the cement composition, the method for producing the cement composition, and the method for producing a concrete product of the present invention will be described in detail.
[0011] 1. Strength enhancer for cement The strength-enhancing material for cement of the present invention is a strength-enhancing material for cement that contains at least awin, belite, and anhydrous gypsum, and contains 36 to 49 parts by mass of awin, 18 to 25 parts by mass of belite, and has a molar ratio of the anhydrous gypsum content / awin content of 2.5 to 6.0. If the content of Awin is less than 36 parts by mass, the initial strength development is low, and if it exceeds 49 parts by mass, the working time for pouring concrete and the like cannot be secured. If the content of belite is less than 18 parts by mass, the working time for pouring concrete and the like cannot be secured, and if it exceeds 25 parts by mass, the initial strength development decreases. If the molar ratio of the anhydrous gypsum content / Awin content is outside the above range, the initial strength development decreases. Even if the mixing ratio of the cement strength enhancer and cement deviates in the mixing process of the cement strength enhancer and cement described below, the strength of the concrete is easily kept constant, and the strength does not easily fluctuate. The content of the awin is preferably 38 to 48 parts by mass, more preferably 40 to 47 parts by mass, and the content of the belite is preferably 19 to 25 parts by mass, more preferably 20 to 23 parts by mass. The molar ratio of the content of the anhydrite / the content of the awin is preferably 2.6 to 5.0, more preferably 2.7 to 4.5, and further preferably 2.8 to 3.5. The anhydrous gypsum is not particularly limited, but is preferably type II anhydrous gypsum from the viewpoint of improving strength development.
[0012] The free lime content in the strength enhancer for cement is preferably 0.5% by mass or less. If the free lime content exceeds 0.5% by mass, there are cases where the time required for work such as pouring concrete cannot be secured.
[0013] Furthermore, the content of the ferrite phase in the strength enhancer for cement is preferably 10 mass% or less, and more preferably 2 to 5 mass%. If the content of the ferrite phase exceeds 10 mass%, the initial strength of the concrete may decrease.
[0014] Furthermore, the Blaine specific surface area of the cement strength enhancer is preferably 4200 to 4600 cm 2 / g. The Blaine specific surface area is 4200 cm 2 At less than 4600cm / g, the initial strength development is low. 2 If the content exceeds 1 / g, it may not be possible to ensure sufficient time for work such as pouring concrete.
[0015] Next, a method for producing the cement strength enhancer will be described. Raw materials such as anhydrous gypsum, bauxite, and limestone are mixed to obtain the mineral composition of the cement strength enhancer according to the following formulas (1) to (5), and then calcined in a normal calcination furnace used for calcining cement, such as a rotary kiln, at a calcination temperature (maximum calcination) of 1250 to 1350°C to produce clinker containing at least Awin (hereinafter referred to as "Awin clinker"). If the calcination temperature is less than 1250°C, the calcination degree of the Awin clinker will be insufficient, and if the calcination temperature exceeds 1350°C, it will be over-calcined, and both of these may result in a decrease in major quality characteristics such as setting and strength development. Awin (C4A3$) = Al2O3 × 1.995 - C4AF × 0.473 (1) Belite (C2S) = SiO2 × 2.867 (2) Ferrite phase (C4AF) = Fe2O3 × 2.693 (3) Free lime (f.CaO)=CaO-C4AF×0.522-C4A3$×0.368-C2S×0.651-C$×0.411 ···(4) Anhydrite (C$)=SO3×1.700-C4A3$×0.223 ···(5) However, the chemical formulas in the formulas (1) to (5) indicate the content (mass %) of the compound represented by the chemical formula. The contents of Awin, belite, ferrite phase, free lime, and anhydrous gypsum in the Awin clinker after firing are calculated by measuring the chemical composition in the Awin clinker and using the chemical composition and the above formulas (1) to (5). If the belite or gypsum in the cement strength enhancer is insufficient, it is advisable to add them.
[0016] 2. Cement composition The cement composition of the present invention is a cement composition containing the strength enhancer for cement and cement, and contains at least 8 to 20 mass% of Awin, 25 to 47 mass% of alite, and anhydrous gypsum, and the molar ratio of the content of the anhydrous gypsum / the content of Awin is 2.5 to 6.0, and the Blaine specific surface area is 3200 to 3700 cm. 2 / g. If the awin content is less than 8% by mass, the initial strength development is low, and if it exceeds 20% by mass, the working time for pouring the concrete and the fluidity of the concrete cannot be ensured. If the alite content is less than 25% by mass, the initial and medium-term strength development is reduced, and if it exceeds 47% by mass, the long-term strength development may be reduced. If the molar ratio of the anhydrite content / awin content is outside the above range, the initial strength development is reduced. Furthermore, if the Blaine specific surface area is less than 3200 cm 2 At less than 3700cm / g, the initial strength development is low. 2 If the content exceeds 1 / g, it may not be possible to ensure sufficient time for work such as pouring concrete. The content of the awin is preferably 9 to 17.5% by mass, more preferably 9.5 to 15% by mass. The content of the alite is preferably 30 to 45% by mass, more preferably 34 to 40% by mass. The molar ratio of the anhydrous gypsum content / the awin content is preferably 2.6 to 5.0, 2.7 to 4.5, more preferably 2.8 to 3.5. The Blaine specific surface area of the cement composition is preferably 3300 to 3600 cm. 2 / g. In other words, the cement composition is a composition containing 20 to 45 parts by mass of the strength enhancer for cement and 55 to 80 parts by mass of cement.
[0017] The free lime content in the cement composition is preferably 1% by mass or less, more preferably 0.1 to 0.5% by mass. If the free lime content exceeds 1% by mass, it may not be possible to ensure sufficient time for work such as pouring concrete.
[0018] The content of the aluminate phase in the cement composition is preferably 4 to 8% by mass. If the content of the aluminate phase is less than 4% by mass, the initial strength development decreases, and if it exceeds 8% by mass, there are cases where the working time for pouring concrete and the like cannot be secured.
[0019] The total content of alite and awin in the cement composition is preferably 45 to 55 mass%, more preferably 48 to 54 mass%. If the total content of alite and awin is less than 45 mass%, the initial strength development decreases, and if it exceeds 55 mass%, it may not be possible to ensure sufficient work time for pouring concrete, etc.
[0020] Furthermore, the content of the ferrite phase in the cement composition is preferably 5 to 15 mass%, and more preferably 7 to 11 mass%. If the content of the ferrite phase is less than 5 mass%, the fluidity may decrease, and if it exceeds 15 mass%, the initial strength may decrease. The use of the cement composition of the present invention is not particularly limited, but in consideration of strength development and fluidity (pot life), it is preferably used in concrete products.
[0021] 3. Manufacturing method of cement composition The cement composition of the present invention can be produced by mixing 20 to 45 parts by mass of a strength enhancer for cement and 55 to 80 parts by mass of cement, preferably 25 to 40 parts by mass of a strength enhancer for cement and 60 to 75 parts by mass of cement, but is not limited thereto. The cement composition of the present invention contains at least 8 to 20% by mass of awin, 25 to 47% by mass of alite, and anhydrous gypsum, and has a molar ratio of the content of the anhydrous gypsum / the content of awin of 2.5 to 6.0 and a Blaine specific surface area of 3200 to 3700 cm. 2 Using the Awin clinker, a cement composition can be produced by any one of the following grinding and mixing methods (i) to (iii). (i) The Awin clinker is pulverized to obtain a pulverized material, and then the pulverized material is mixed with cement to produce a cement composition. The method (i) is suitable for the case where a concrete product company purchases a strength enhancer for cement and mixes it with cement at a concrete product factory. Since the Awin clinker contains the amount of anhydrous gypsum specified in the present invention, the method of mixing the ground material with commercially available Portland cement or other cement is preferable because it simplifies the manufacturing process and facilitates quality control at the concrete product factory. (ii) The Awin clinker and the cement clinker are mixed and then ground together to produce a cement composition. The method (ii) has high production efficiency since the production can be completed in only one grinding step. (iii) The Awin clinker and the cement clinker are ground separately or a plurality of them are ground simultaneously to produce a cement composition. In the above (i) to (iii), if the cement composition contains insufficient gypsum, it is advisable to add gypsum.
[0022] The cement and cement clinker may be one or more selected from ordinary Portland cement, high-early-strength Portland cement, moderate-heat Portland cement, and ecocement, as well as their clinkers. Of these, ordinary Portland cement is preferred because it is easy to keep the strength of the concrete constant and the strength does not easily fluctuate even if the blending ratio of the cement strength enhancer and cement is changed. The contents (mass%) of alite, belite, aluminate phase, and ferrite phase in these cements are calculated using the Bogue formulas (i) to (iv) below. C3S=4.07×CaO-7.60×SiO2-6.72×Al2O3-1.43×Fe2O3-2.85×SO3...(i) C2S=2.87×SiO2-0.754×C3S (ii) C3A=2.65×Al2O3-1.69×Fe2O3···(iii) C4AF = 3.04 × Fe2O3 (iv) In the formulas (i) to (iv), the chemical formulas indicate the content (mass%) of the compound represented by each chemical formula in the cement. In addition, in Table 3, C$0.5H indicates gypsum hemihydrate, and C$2H indicates gypsum dihydrate. In addition, the free lime in cement is measured in accordance with JCAS I-01:1997 "Method for determining free calcium oxide." Regardless of the method for producing the cement composition, the Blaine specific surface area of the cement composition is 3200 to 3700 cm 2 / g is preferred.
[0023] 4. Manufacturing method of concrete products The method for producing a concrete product of the present invention includes a kneading step of kneading the cement composition with at least fine aggregate, coarse aggregate, and water to obtain an unhardened concrete composition, a filling step of filling a formwork with the unhardened concrete composition, a curing step of curing the unhardened concrete composition at a temperature of 10 to 50°C to obtain a hardened concrete composition, and a demolding step of demolding the hardened concrete composition. The curing temperature is 10°C to 50°C, preferably 10°C to 40°C, and more preferably 10°C to 30°C. Even at such a low temperature, it is possible to obtain a strength equal to or greater than the demolding strength of a steam-cured concrete product.
[0024] The curing time (the time from mixing to demolding) is 3 to 12 hours, preferably 4 to 10 hours, and more preferably 5 to 7 hours. In these times equivalent to those required for steam-cured concrete products, it is possible to obtain strength equal to or greater than the demolding strength of steam-cured concrete products. In addition, in the manufacturing method of the concrete product of the present invention, various admixtures such as air-entraining agents, water-reducing agents, air-entraining water-reducing agents, high-performance water-reducing agents, and high-performance air-entraining water-reducing agents, as well as various admixtures such as fly ash, silica fume, and blast-furnace slag powder can be used as other materials within the range in which the desired demolding strength is obtained. The kneading method in the kneading step, the type of formwork and the filling method in the filling step, and the curing method in the curing step, such as underwater, sealed, or in air, are not particularly limited, and any commonly used method can be used. EXAMPLES
[0025] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. 1. Manufacturing of strength enhancers for cement Type II anhydrite, bauxite, and limestone were mixed and compressed to obtain the chemical composition shown in Table 1, and pellets (about 20 g each) were produced. The pellets were then placed in an electric furnace and calcined at 1000°C for 30 minutes to remove moisture and carbon dioxide, and then heated to 1350°C at a heating rate of 700°C / hour, and fired at 1350°C for 20 minutes. The pellets were then allowed to cool outside the furnace to produce Awin clinker. Next, the Awin clinker was crushed to obtain a granular material having a Blaine specific surface area of 4500 cm 2 The mineral composition of the cement strength enhancer is shown in Table 2. The mineral compositions of the strength enhancers for cement shown in Table 2 were calculated from the above formulas (1) to (5) using the chemical compositions of the strength enhancers for cement measured by X-ray fluorescence analysis and shown in Table 1. Strength enhancer A9 was produced by mixing strength enhancer A1 and gypsum dihydrate in a ratio of 70:30 (mass ratio).
[0026] [Table 1]
[0027] [Table 2]
[0028] 2. Preparation of cement composition The cement strength enhancer and Blaine specific surface area are 3200 cm 2 / g ordinary Portland cement was mixed with the strength enhancer for cement in accordance with the contents of the strength enhancer for cement shown in Table 3 to produce a cement composition having the mineral composition shown in Table 3. The mineral composition of the cement composition shown in Table 3 was calculated based on the mixing ratio of the strength enhancer for cement and ordinary Portland cement, using the mineral composition of the strength enhancer for cement calculated by the above formulas (1) to (5) and the mineral composition of ordinary Portland cement calculated by the following Bogue formulas (i) to (iv). The mineral composition of ordinary Portland cement was calculated using the Bogue formulas (i) to (iv) above, based on the chemical composition of ordinary Portland cement measured using X-ray fluorescence analysis. The quantitative determination of gypsum hemihydrate and gypsum dihydrate was performed in accordance with the thermogravimetric analysis method described in the following document. [References] Satoshi Hirose, Mari Takahashi, Hiroaki Matsuzato, Junji Asami, Yukinori Yamazaki, and Yoshishi Asaga: Quantitative analysis of gypsum hemihydrate and dihydrate in cement by thermogravimetric analysis, Inorganic Materials, Vol. 2, No. 254, pp. 14-17, (1995) The amount of free lime in the cement was measured in accordance with JCAS I-01:1997 "Method for determining free calcium oxide."
[0029] [Table 3]
[0030] 3. Measurement of compressive strength and flow value (1) Compressive strength measurement In accordance with JIS R 5201 "Physical test methods for cement," the mortar prepared using the cement composition produced above was placed in a formwork with an inner diameter of 50 mm and a height of 100 mm, sealed and cured at 20°C for 6 hours, and then removed from the formwork to measure the compressive strength. For reference, mortar made with ordinary Portland cement was placed in a formwork with an inner diameter of 50 mm and a height of 100 mm, and after heat curing to simulate the first cycle (4-hour steam curing) in a two-turn manufacturing process, it was demolded and the compressive strength was measured. Specifically, a thermohygrostat manufactured by Espec Corporation was used as the curing tank, and the humidity was set to 98% relative humidity, which is the upper limit of this device. Pre-curing was performed at 20°C for 2 hours, with a heating rate of 20°C / h and a maximum temperature of 60°C. After reaching the maximum temperature, the temperature was not maintained and the mortar was gradually cooled in the tank. Then, 2 hours after reaching the maximum temperature, the mortar was taken out of the thermohygrostat and demolded, and then subjected to a compressive strength test (reference example). (2) Flow value measurement According to JIS R 5201 "Physical Testing Methods for Cement", the flow values of mortars prepared using the cement compositions prepared above and mortars prepared using ordinary Portland cement were measured. The results are shown in Table 4.
[0031] [Table 4]
[0032] As shown in Table 4, the cement composition of the present invention was able to obtain strength at least equal to that obtained with steam curing at an age of 6 hours without steam curing, and was also able to obtain the fluidity (workability) required in concrete product factories.
Claims
1. A cement composition comprising 20 to 45 parts by mass of a cement strength enhancer and 55 to 80 parts by mass of cement, The composition contains at least 9.5 to 15 mass% awin, 34 to 40 mass% alite, 45 to 55 mass% awin and alite in total, 4 to 8 mass% aluminate phase, 5 to 15 mass% ferrite phase, and anhydrous gypsum, and the molar ratio of the anhydrous gypsum content / awin content is 2.5 to 6.0, and the Blaine specific surface area is 3200 to 3700 cm 2 / g of the cement composition. [Strength enhancer for cement] A strength enhancer for cement comprising at least awin, belite, and anhydrous gypsum, The composition contains 36 to 49 parts by mass of awin, 18 to 25 parts by mass of belite, and the molar ratio of the anhydrous gypsum content / the awin content is 2.5 to 6.
0.
2. The cement composition according to claim 1, further comprising 1% by mass or less of free lime.
3. The cement composition according to claim 1 or 2, wherein the cement composition is for use in concrete products.
4. A mixing step of mixing the cement composition according to any one of claims 1 to 3 with at least fine aggregate, coarse aggregate, and water to obtain an unhardened concrete composition; A filling step of filling the unhardened concrete composition into a formwork; a curing step of curing the unhardened concrete composition at a temperature of 10 to 50°C to obtain a hardened concrete composition; and A demolding step of demolding the hardened body of the concrete composition; A method for producing a concrete product comprising at least the steps of:
Citation Information
Patent Citations
Cement composition of low shrinkage and high strength
JP1997048649A
Anhydrous gypsum containing fired material and solidification material
JP2011051876A
Method for manufacturing rapid-hardening agent and concrete product
WO2013054604A1